Hyperglycemia-induced attenuation of rectal perception depends upon pattern of rectal balloon inflation. Digestive Diseases and Sciences - (:unkn) unknown (My University, 1997)
This study investigated the effects of acute hyperglycemia on conscious rectal perception in response to two different rectal distension paradigms. Eleven healthy males were studied in random order on two separate days during euglycemia and hyperglycemia with blood glucose concentrations clamped to 3.8 +/- 0.6 and 14.8 +/- 0.86 mmol/liter, respectively. In order to evoke sensory responses, rapid phasic and ramplike distensions were applied to an intrarectal balloon. Rectal sensation thresholds for initial sensation, sensation of stool and discomfort, and sensory intensities were recorded. Additionally, anorectal motor responses were investigated during phasic distension. Acute hyperglycemia did not modify rectal sensory pressure thresholds and perception scores in response to phasic distension. Neither did hyperglycemia alter the resting anal sphincter pressure, the pressure threshold for eliciting the rectoanal inhibitory reflex, or the maximal anal squeeze pressure. In contrast, hyperglycemia attenuated rectal perception in response to ramplike distension. The pressure thresholds, 10.0 +/- 1.8 and 17.0 +/- 3.6 mm Hg for initial sensation and discomfort, respectively, during hyperglycemia were significantly higher than the corresponding thresholds of 4.4 +/- 1.4 and 11.4 +/- 1.9 mm Hg observed during euglycemia (P < 0.01). Higher rectal pressures were observed at all intensities of sensation of stool and discomfort during hyperglycemia than those obtained during euglycemia (P < 0.01). Hyperglycemia did not alter the compliance of the rectum. The results of this study demonstrate that acute hyperglycemia attenuates rectal perception, and this attenuation depends upon the type of distension employed. Our findings also demonstrate that anal sphincter motor function is not appreciably modified by hyperglycemia.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; GASTROENTEROLOJİ VE HEPATOLOJİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; GASTROENTEROLOGY & HEPATOLOGY; MEDICINE, GENERAL & INTERNAL; Aile Sağlığı; Temel Bilgi ve Beceriler; Tıbbi Bilişim; Genel Sağlık Meslekleri; Patofizyoloji; Gastroenteroloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Hepatoloji; Family Practice; Fundamentals and Skills; Health Informatics; General Health Professions; Pathophysiology; Gastroenterology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Hepatology